SWOT Based Service Quality Improvement Strategy at PT. FOKUS KUALITAS UTAMA - M. Indra Fauzi; Nuruni Ika Kusuma Wardani (Pusat Riset dan Inovasi Nasional, 2024)
In a highly competitive world, companies face numerous challenges. For service-based companies, success is determined by the quality of their services. PT. FOKUS KUALITAS UTAMA is a business consulting firm that assists in enhancing the performance of human resources within a company or organization. The objective of this research is to identify the internal and external factors that can improve the service quality in PT. FOKUS KUALITAS UTAMA. This study utilizes qualitative methods and collects primary and secondary data through observation, interviews, literature review, and SWOT analysis using IFAS and EFAS tables. The research findings indicate that PT. FOKUS KUALITAS UTAMA services fall within Quadrant I, implying an aggressive strategy.